The Coevolution of Institutional Entrepreneurship: A Tale of Two Theories - Pacheco, Desirée F.; York, Jeffrey G.; Dean, Thomas J.; Sarasvathy, Saras D. (Journal of Management, 2010)
This article provides a review and analysis of institutional entrepreneurship research with a focus on the emergence of this literature within two largely divergent streams: sociology-based institutional theory and economics-based institutional economics. The authors completed a review of 141 articles from these concurrent, but unlinked, research streams to understand how their integration might contribute to the further understanding of institutional entrepreneurship. Each stream is reviewed on its respective approaches to the following topics: the nature of the institutional entrepreneur, the types of institutions addressed, the determinants of institutional entrepreneurship, the mechanisms used in the process, and the empirical focus of each stream. The article recommends greater assimilation of the two streams and discusses specific opportunities for conceptual integration. Finally, the article offers an agenda for incorporating entrepreneurship research into the study of institutional entrepreneurship. Findings from this review suggest that while institutional economics focuses mostly on the antecedents and outcomes of institutional entrepreneurship, the institutional theory perspective is more concerned with the process and mechanisms that drive such change. The authors also suggest that entrepreneurship theory can greatly advance our understanding of institutional entrepreneurship by informing whether and how opportunities for institutional change are recognized, discovered, and created, as well as by providing insights on the antecedents and mechanisms of such activity. Most important, integrating the unique perspectives and domains of institutional theory, institutional economics, and entrepreneurship research in the study of institutional entrepreneurship provides substantial opportunity for expanding our understanding of the concept and its implications.